Nilotinib combined with interleukin-2 mediates antitumor and immunological effects in a B16 melanoma model - Geisler, K.; Reischer, Anna; Kroeger, I.; Jacobs, B.; Meinhardt, K.; Bauer, R.; Ryffel, B.; Mackensen, Andreas; Ullrich, E. (Oncology Reports, 2014)
The immune system contributes to tumor cell killing which can be enhanced by cancer chemotherapeutics and immune modulatory pharmaceuticals such as tyrosine kinase inhibitors (TKIs). Recently, the beneficial effect of natural killer (NK) cells was demonstrated when combining interleukin-2 (IL-2) with the TKI imatinib. The aim of the present study was to address the antitumor and immunological effects of recently approved TKIs. Therefore, we focused on the comparison of the efficacy between imatinib and nilotinib in combination with IL-2 in a murine B16F10 melanoma model. Both TKIs possessed antitumor activity in vivo. However, the combination of nilotinib and IL-2 showed a superior outcome. Importantly, both the use of immunodeficient Rag2?c-/- mice, which lack T-lymphocytes, B-lymphocytes and NK cells, as well as NK cell-depletion in C57Bl/6 mice reduced the therapeutic effect of nilotinib. Flow cytometry revealed a significant increase in the IFN-?-producing CD27+ NK cell subpopulation following treatment with nilotinib and IL-2. Furthermore, the therapeutic antitumor effect of nilotinib/IL-2 was completely lost in IFN-?-/- mice. In summary, we suggest that nilotinib combined with IL-2 confers high antitumor activity involving the subset of IFN-?-producing CD27+ NK cells. These new insights are of high importance for the understanding and development of immunotherapeutic protocols using TKIs.
EVALuna2:25694